2019
DOI: 10.5194/amt-2019-461
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shipborne MAX-DOAS measurements for validation of TROPOMI NO<sub>2</sub> products

Abstract: Abstract. Tropospheric NO2 and stratospheric NO2 vertical columns are important TROPOMI data products. In order to validate the TROPOMI NO2 products, KNMI MAX-DOAS instruments have measured NO2 on ship cruises over the Atlantic and the Pacific oceans. The MAX-DOAS instruments have participated in five cruises on-board R.V. Sonne (in 2017 and 2019) and R.V. Maria S. Merian (in 2018). The MAX-DOAS measurements were acquired in 7 months and spanned about 300° in longitude and 90° in latitude. During the cruises t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Based on these results, we assume a low bias of 37 % can be mitigated by ~ 12 % through the use of high spatial resolution profiles, for a resulting total low bias of 25 %. This bias is likely not valid over pristine areas, where validation studies show lower biases in TROPOMI NO 2 ( Verhoelst et al, 2021 ; P. Wang et al, 2020 ; Zhao et al, 2020 ); nonetheless, we previously observed in Souri et al (2020a) that the low signal-to-noise ratios of those column amounts resulted in small changes in the top-down emissions. We assume the errors of observations originate from two main sources: (i) the precision error provided with the data ( e precision ) and (ii) a fixed error estimated from comparisons to in situ measurements ( e const ).…”
Section: Measurements Modeling and Methodsmentioning
confidence: 75%
“…Based on these results, we assume a low bias of 37 % can be mitigated by ~ 12 % through the use of high spatial resolution profiles, for a resulting total low bias of 25 %. This bias is likely not valid over pristine areas, where validation studies show lower biases in TROPOMI NO 2 ( Verhoelst et al, 2021 ; P. Wang et al, 2020 ; Zhao et al, 2020 ); nonetheless, we previously observed in Souri et al (2020a) that the low signal-to-noise ratios of those column amounts resulted in small changes in the top-down emissions. We assume the errors of observations originate from two main sources: (i) the precision error provided with the data ( e precision ) and (ii) a fixed error estimated from comparisons to in situ measurements ( e const ).…”
Section: Measurements Modeling and Methodsmentioning
confidence: 75%